Islam, Sharia and Alternative Dispute Resolution : Mechanisms for Legal Redress in the Muslim Community - Keshavjee, Mohamed M. (London I.B. Tauris & Co. Ltd., 2014)
This groundbreaking book shows that Shari'a and its 'fiqh' (laws set forward by various Islamic legal schools) comprise a far more nuanced matrix of interpretations than is often assumed to be the case.
Include Figures, Appendix, Notes, Glossary, Bibliography and Index.
Mechanisms for Legal Redress in the Muslim Community.
Keywords: Islamic countries -- Dispute resolution (Law) -- Islamic law